Eficiência do processo foto-Fenton solar em um fotorreator piloto no pós-tratamento do lixiviado do aterro sanitário metropolitano de João Pessoa - Batista, Mariana Medeiros (2016)
The solar photo-Fenton process appears as an attractive alternative to post-treatment of landfill leachate to reduce the recalcitrant organic load of these effluents and, at the same time, to reduce energy costs of treatment by the use of a clean, renewable and free energy source. In this way, the present study aimed to evaluate the efficiency of the solar photo- Fenton process in the final physicochemical and toxicological quality of the biologically pretreated leachate from the landfill of João Pessoa city using a pilot-scale photoreactor. Initially, the operating conditions were investigated (flow, reaction time and pH adjustment) for the solar photo-Fenton process in pilot-scale. For this, three tests were performed with different flow rates (test1=65L.min-1, test2 = 48L.min-1, test3 = 35L.min-1). Then, the test 4 was carried to evaluate the reaction time process (60, 120 and 180 minutes) and the influence of pH adjustment (pH8) in the samples after the process. Under defined conditions, the efficiency of the solar photo-Fenton process was evaluated in terms of physicochemical and toxicological parameters (test 5). The influence of solar photolysis treatment was also observed. As a result, it was verified that the flow does not interfere directly in the removal of COD; then the minimum flow (35L.min-1) was adopted. In 60 minutes of reaction, it was possible to obtain high COD (76.1%) and color (93.45%) removals, so, this time was chosen for the process. The pH adjustment procedure was adopted to standardize the phototreated samples, since it increased the COD removal around 4%. In general, there was no change in the physicochemical characteristics of the leachate after the solar photolysis process. The solar photo-Fenton process provided high removals of color (87.5%), COD (81.7%) and recalcitrance, in terms of BOD5/COD (which increased from 0.12 to 0.32) and aromatic compounds (A254: 87,1% and A280: 87,74%). In addition, the solar photo-Fenton process reduced 76% of the leachate phytotoxicity on the lettuce plant (Lactuca sativa), in terms of EC50. In that way, it can be concluded that the solar photo-Fenton process was efficient when applied in pilot-scale, acting as an interesting post-treatment alternative for reduction of COD, color, recalcitrance and toxicity from landfill leachate.